2016
DOI: 10.1098/rspb.2016.1364
|View full text |Cite
|
Sign up to set email alerts
|

Lifespan, growth rate, and body size across latitude in marine Bivalvia, with implications for Phanerozoic evolution

Abstract: Mean body size in marine animals has increased more than 100-fold since the Cambrian, a discovery that brings to attention the key life-history parameters of lifespan and growth rate that ultimately determine size. Variation in these parameters is not well understood on the planet today, much less in deep time. Here, we present a new global database of maximum reported lifespan and shell growth coupled with body size data for 1 148 populations of marine bivalves and show that (i) lifespan increases, and growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(130 citation statements)
references
References 38 publications
(43 reference statements)
8
122
0
Order By: Relevance
“…When applying the standard density of aragonite (2.93 g/cm 3 ; Graus, 1974), this equates to an average aragonite secretion rate of 240 g/year and a maximum secretion rate of 1,188 g/year for our largest specimen of C. giganteum (E3). These are exceptionally high rates of growth compared to other marine calcifiers, such as corals (~5–16 g/cm 2 /year; Baker & Weber, 1975; Hetzinger et al, 2006), bivalves (~2–12 mm/year depending on latitude; Ridgway et al, 2011; Moss et al, 2016; with maxima of 4.1 g/cm 2 /year for Tridacna gigas and 214 g/year for extinct rudist bivalves; Steuber, 2000), and other gastropods (growth rates of 5–30 mm/year for nongiant gastropods; Frank, 1969; ~80 or ~63 g/year for giant gastropod L. gigas ; Berg, 1976; and ~35 g/year for the fastest‐growing turritellid species Turritella abrupta ; Anderson & Allmon, 2020; see also Figure 7). C. giganteum therefore likely ranks as one of the fastest growing mollusks known to date.…”
Section: Resultsmentioning
confidence: 99%
“…When applying the standard density of aragonite (2.93 g/cm 3 ; Graus, 1974), this equates to an average aragonite secretion rate of 240 g/year and a maximum secretion rate of 1,188 g/year for our largest specimen of C. giganteum (E3). These are exceptionally high rates of growth compared to other marine calcifiers, such as corals (~5–16 g/cm 2 /year; Baker & Weber, 1975; Hetzinger et al, 2006), bivalves (~2–12 mm/year depending on latitude; Ridgway et al, 2011; Moss et al, 2016; with maxima of 4.1 g/cm 2 /year for Tridacna gigas and 214 g/year for extinct rudist bivalves; Steuber, 2000), and other gastropods (growth rates of 5–30 mm/year for nongiant gastropods; Frank, 1969; ~80 or ~63 g/year for giant gastropod L. gigas ; Berg, 1976; and ~35 g/year for the fastest‐growing turritellid species Turritella abrupta ; Anderson & Allmon, 2020; see also Figure 7). C. giganteum therefore likely ranks as one of the fastest growing mollusks known to date.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, life spans of bivalve species are observed to be significantly shorter in the tropics than near the poles, which was explained by their faster metabolism related to better food availability (Moss et al, 2016). Consequently, the longest-lived Glycymeris spp.…”
Section: Longevitymentioning
confidence: 99%
“…Bivalves, which follow a uniform developmental progression from the larval stage, differ from mammals in that growth rate is not related to asymptotic adult size [7]. Nonetheless, there is a robust negative relationship between growth rate and longevity in this class [6,7].…”
Section: Interspecies Comparisons Linking Growth Rate and Longevitymentioning
confidence: 95%
“…Arctica islandica, e.g., has been reported to be capable of living past 500 years. Ridgway et al [6], investigating 56 species, report a weak, although significant, relationship between maximum life span and asymptotic shell length, while a larger study involving 297 species reported no relationship [7].…”
Section: Interspecies Comparisons Linking Body Mass and Longevitymentioning
confidence: 98%